The effect of family-centered empowerment model on burden of care in parents and blood glucose level of children with type I diabetes family empowerment on burden of care and HbA1C - Samira Rostaminasab; Monirsadat Nematollahi; Yones Jahani; Roghayeh Mehdipour-Rabori (BMC, 2023)
Abstract Background Parents play a critical role in caring for their children with diabetes and bear a significant burden of care. Health education has increasingly focused on empowering parents through new strategic methods. The present study aims to investigate the impact of a family-centered empowerment model on the burden of care in parents and blood glucose levels of children with type I diabetes. Methods An interventional study was conducted in Kerman, Iran, where 100 children with type I diabetes and their parents were randomly selected as participants. The study aimed to implement a family-centered empowerment model in the intervention group, which consisted of four stages (educational phase, increasing self-efficacy, improving self-confidence, and evaluation) over a period of one month. The control group received routine training. The Zarit Caregiver Burden questionnaire and HbA1c log sheet were utilized to evaluate the effectiveness of the intervention. Questionnaires were administered before, after, and two months post-intervention, and data were analyzed using SPSS 15. Non-parametric tests were employed, and statistical significance was set at p < 0.05. Results Before the study, no significant differences in demographic variables, level of burden of care, or HbA1C levels were observed between the two groups (p < 0.05). After the intervention, the burden of care score in the intervention group was significantly lower than that in the control group, both immediately post-intervention and two months later (P < 0.0001). Additionally, the median HbA1C levels in the intervention group were significantly lower than those in the control group after two months (6.5 in the intervention group and 9 in the control group) (P < 0.0001). Conclusion The findings of this study suggest that the implementation of a family-centered empowerment model is an effective strategy for reducing the burden of care on parents of children with type 1 diabetes and for controlling the HbA1C levels of these children. Based on these results, it is recommended that healthcare professionals consider incorporating this approach into their educational interventions.